PENGARUH PEMBERDAYAAN BADAN USAHA MILIK DESA (BUMDES) SYARIAH KEMBANG SETANJUNG TERHADAP PENINGKATAN EKONOMI MASYARAKAT DESA TANJUNG MEDAN - Dermawan (Jurnal Ilmiah Cano Ekonomos, 2023)
BUMDes empowerment in this case includes the process of empowering development potentials that exist in the village that originate "from, by, and for the community" or in other words implemented in a participatory manner capable of carrying out development and increasing people's welfare optimally. The purpose of this study is how much influence does the empowerment of Kembang Setanjung Syariah BUMDes have on increasing the economy of the people of Tanjung Medan Village? The research used in this research is quantitative-descriptive research. The population of this research is 1000 customers and the sample of this research is 200 customers. The sampling technique used is purposive sampling. Data collection techniques using observation and questionnaires. The results of the study showed that there was a positive influence between the empowerment of Kembang Setanjung Syariah BUMDes on improving the economy of the people of Tanjung Medan Village. This result is indicated by a coefficient value of 0.879 which is greater than the rtable of 0.310. In addition, the value of Fcount = 2.367. While Ftable = 3.10 with a significance value = 0.023 <0.05. The Ho criterion is rejected if Fcount > Ftable with Î± = 0.05 (5%) with a value of 2,367> 3.10. The effective contribution is obtained from the coefficient of determination (R2) of 85.3%. So, it can be interpreted that 85.3% of the empowerment of the Syariah Kembang Setiajung BUMDes has a positive effect on improving the economy of the people of Tanjung Medan Village